The effect of topical capsaicin-induced sensitization on heat-evoked cutaneous vasomotor responses - Nielsen, Thomas A (e-Century Publishing Corporation, 2013)
Brief, localized, cutaneous, non-painful thermal stimuli can evoke a transient vasomotor response, causing increased cutaneous blood flow and elevated skin temperature. The aims of this study were to investigate 1) if cutaneous sensitization by topical application of capsaicin (TRPV1 receptor agonist) can facilitate the size, duration and spatial extent of this vasomotor response and 2) if males and females respond differently. Thermal pulses (43°C for 60 seconds) were applied on left/right volar forearms of 15 age-matched males and females. Skin temperature and cutaneous blood flow were measured 1, 5, 10, 15, and 30 minutes after heat application before and after topical capsaicin (1%, 30 min application) with contralateral arm serving as the control. Recordings were made from the region of interest at distances of 2, 4, 6, 8, and 10 cm from the capsaicin application site. Sensitization significantly enhanced skin temperature for up to 30 min and compared with non-sensitized skin at 10 min. Females showed the strongest response after sensitization, but the response lasted longer and spread more widely in males. The blood flow responses were significantly longer after capsaicin (from 5 to 30 minutes after thermal application). This increased blood flow extended outside the treated area up to 10 min after stimulation. After sensitization, the area under the blood flow response curves showed significantly stronger responses in females, spreading 4 cm outside the stimulation site. Cutaneous sensitizing caused prolonged and spatially expanded vasomotor responses to standardized thermal stimulation with sex specific differences.